2013
DOI: 10.1002/jsfa.6030
|View full text |Cite
|
Sign up to set email alerts
|

Activities of free and encapsulated Lactobacillus acidophilusLA5 or Lactobacillus casei 01 in processed longan juices on exposure to simulated gastrointestinal tract

Abstract: Both encapsulated probiotics along with processed longan juice led to significant increases in colon lactobacilli, lactic acid and SCFA formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 68 publications
2
15
0
Order By: Relevance
“…Zhang et al (2009) reported that the concentration of accumulated Se in the biomass of Bifidobacterium animalis 01 was approximately 1 mg/g in a culture exposed to 10 mg/L of Na 2 SeO 3 in the culture medium. The concentrations obtained in the present study for all 6 Lactobacillus strains were above those reported by Calomme et al (1995a) for both Se concentrations (30 and 60 mg/L) used in the growth test. However, the highest levels of bioaccumulated Se in L. paracasei ML13, L. paracasei ML135, and L. paracasei CH139 grown in medium enriched with 60 mg/L of Se were similar to those reported in other studies (Xia et al, 2007;Zhang et al, 2009).…”
Section: Lab Growth and Se Bioaccumulationsupporting
confidence: 55%
See 2 more Smart Citations
“…Zhang et al (2009) reported that the concentration of accumulated Se in the biomass of Bifidobacterium animalis 01 was approximately 1 mg/g in a culture exposed to 10 mg/L of Na 2 SeO 3 in the culture medium. The concentrations obtained in the present study for all 6 Lactobacillus strains were above those reported by Calomme et al (1995a) for both Se concentrations (30 and 60 mg/L) used in the growth test. However, the highest levels of bioaccumulated Se in L. paracasei ML13, L. paracasei ML135, and L. paracasei CH139 grown in medium enriched with 60 mg/L of Se were similar to those reported in other studies (Xia et al, 2007;Zhang et al, 2009).…”
Section: Lab Growth and Se Bioaccumulationsupporting
confidence: 55%
“…The differences in the growth capacity and Se bioaccumulation of the studied strains ( L. paracasei CH135,and L. paracasei CH139) in the growth and tolerance tests (Tables 1 and 2 and Figures 1 and 2) and the divergences or similarities (or both) compared with data from the literature (Calomme et al, 1995a;Xia et al, 2007;Zhang et al, 2009;Pieniz et al, 2011Pieniz et al, , 2017Deng et al, 2015;Palomo-Siguero et al, 2016) are plausible given that the binding of metal or metalloid ions, such as Se, to the cell wall of LAB and their transport and storage in the cell are mediated by complex processes that depend on the characteristics of the element, the specific physiological properties of each LAB strain, and the physical chemical characteristics of the environment in which the bacteria are grown (Mrvčić et al, 2012). The bioaccumulation process does not depend on temperature or the presence of metabolic energy or metabolic inhibitors but instead depends on the functional groups available on the cell surface, the nature of the ions, and their concentrations and surface charges, cations, and metal ligands, which can occur through 2 different mechanisms: biosorption, which is a passive binding process of the metal to the bacterial cell wall that is not metabolically mediated, and bioaccumulation, which is an active metabolic binding process during which metal ions cross the cell membrane and accumulate within the cell (Vijayaraghavan and Yun, 2008).…”
Section: Lab Tolerance To Sementioning
confidence: 94%
See 1 more Smart Citation
“…Verification of compatibility and adaptability among the selected strains and matrixes is fundamental. Several lactic probiotic products, chiefly the fermented as well as some non-lactic products, have been developed as fruit drinks containing probiotics and have been gaining interest in the global marketplace (KOMATSU; BURITI; SAAD, 2008;CHAIKHAM et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Such effects following supplementation with KMN (Treatment 3) and the latter in combination with B. lactis Bb-12 (Treatment 4) were not of significant difference (P>0.05). Clear correlations between increased levels of beneficial gut bacteria and organic acids (Table 3) in the simulated gastrointestinal environment can be explained by their immunemodulatory and regulative functions, and natural inhibitory effects of common gut pathogens, including Staphylococcus aureus, Clostridium botulinum, Listeria monocytogenes, and some harmful strains of Escherichia coli (Maslowski and Mackay, 2011;Chaikham et al, 2013). Chaikham et al (2012) reported that the probiotics or/and prebiotics possibly produced lowmolecular-weight antimicrobial substances (i.e.…”
Section: Colon Microbial Populations and Pcr-dgce Fingerprintsmentioning
confidence: 99%